Finite element analysis of the biomechanical effects of manipulation of lower limb hyperextension on the sacroiliac joint - Luo, Bangmin; Li, Yikai; Wang, Cheng; Xu, Zhun (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe objective of this study was to explore the effects of four Manipulations of lower limb hyperextension (MLLHs) on the sacroiliac joint (SIJ) and surrounding ligaments.MethodsA three-dimensional finite element model of the pelvis was built. Four MLLHs were simulated. The stresses on the pelvis and SIJ were calculated. The SIJ displacements and ligament strains were analyzed.ResultsUnder MLLH-F1, -F2, -F3 and -F4, the maximum stresses on the pelvis were 49.2, 50.5, 48.6 and 54.0 MPa, and the maximum stresses on the left SIJ were 3.1, 3.2, 3.0 and 3.4 MPa, respectively. The total SIJ displacements were 0.129, 0.164, 0.080 and 0.154 mm under MLLH-F1, -F2, -F3 and -F4, respectively. The four MLLHs all caused different degrees of ligament strain, MLLH-F2 the greatest.ConclusionMLLH-F2 and -F4 caused greater stresses on the pelvis and the SIJ surface. The four MLLHs all produced small SIJ displacements. MLLH-F2 produced the largest SIJ displacement and the greatest ligament strain. These findings can guide the choice of therapy.